Innovations in Teaching Chemistry - Ruzieva Komila Ernazarovna (Peerian Journals Publishing, 2022)
The article discusses modern innovations used in the teaching of chemical sciences, their types, requirements for their use.
Keywords: Innovation; educational activity; ideological innovations; cognitive activity